THE FUNDAMENTALIST DILEMMA: LESSONS FROM THE ISRAELI HAREDI CASE. (6th July 2016) - Fisher, Netanel
Abstract: This article explores the "fundamentalist dilemma, " or how fundamentalist movements participate in secular political systems, especially when they gain prominent political positions that allow them to impose their extreme ideology on the entire society. After analyzing prevailing responses to this dilemma, ranging from political integration to aggressive takeover, the article turns to the case of Israeli Haredim. It explores three models of political integration through which Haredim have applied religious practices in the public sphere: protest, consolidation, and takeover. The study's main finding is that, opposite to a commonly accepted assumption that fundamentalists' integration into secular politics causes them to moderate, the more political power that fundamentalists accrue the stronger is their tendency to promote their religious agenda. Yet the Israeli Haredi case also reveals the limitations of this tendency: fundamentalists often restrain their expansionist instinct when having to take nonfundamentalist reactions into consideration. EL DILEMA FUNDAMENTALISTA: LECCIONES DEL CASO DE LOS JAREDÍES ISRAELÍES: Este artículo investiga el "dilema fundamentalista" o la forma en que los movimientos fundamentalistas intervienen en los sistemas políticos seculares, en especial cuando alcanzan posiciones políticas destacadas que les permiten imponer su ideología extrema a toda la sociedad. Después de analizar las respuestas predominantes a este dilema, que van desde la integración política hasta la toma violenta del poder político, el artículo se vuelca al caso de los jaredíes israelíes. El artículo explora tres modelos de integración política a través de los cuales los jaredíes han aplicado las prácticas religiosas a la esfera pública: protesta, consolidación y toma del poder. La conclusión principal del estudio es que, contrariamente a la suposición comúnmente aceptada de que la integración de los fundamentalistas a la política los hace más moderados, cuanto más poder político adquieren, mayor es su tendencia a promover su agenda religiosa. Sin embargo, el caso de los jaredíes israelíes también revela las limitaciones de esta tendencia: los fundamentalistas suelen refrenar su instinto expansionista cuando tienen que tener en cuenta las reacciones no fundamentalistas.